Clinical and histochemical alterations of the periodontal ligament in gerbils after malocclusion induced - Naves, Leandro Moura Leite; Issa, João Paulo Mardegan; Pitol, Dimitrius Leonardo [UNESP]; Fukada, Sandra Yasuyo; Di Matteo, Miguel Angel Sala; Iyomasa, Mamie Mizusaki (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2007)
The aim of this article is to show the clinical and histochemical alterations of the first periodontal ligament, on the right side, after upper molars teeth extraction on the left side in gerbils. After two months, the periodontal ligaments were removed and processed for histochemical analysis. The data showed that TRAP reaction was able to evidence the osteoclastic activity in the hyperfunction hemimandible, right side, explaining the functional changes in the periodontal ligament after teeth extraction, and a little gingival recession and radicular exposure of teeth without function was observed at inferior molars of the left side.
Keywords: Histochemistry; Malocclusion, gerbil; Meriones unguiculatus; Periodontal ligament